Developing a Precautionary Management Approach for the Eastern Canada-West Greenland Population of Bowhead Whales (Balaena mysticetus) - Ferguson, Steven H.; Higdon, Jeff W.; Hall, Patricia A.; Hansen, Rikke Guldborg; Doniol-Valcroze, Thomas (Frontiers in Marine Science, 2021)
Sound wildlife management is based on clearly defined objectives and prioritized actions that can incorporate new stock assessment information as it becomes available. For example, biological reference points can inform management objectives and in turn guide short-term management decisions (Punt, 2006; Curtis et al., 2015). International agreements have established that the Precautionary Approach (PA) should be applied to management of the environment and of fisheries, e.g. the Rio Declaration, the Cancun Summit, the United Nations Agreement on Straddling Fish Stocks and Highly Migratory Fish Stocks, the United Nations Food and Agriculture Organization Code of Conduct for Responsible Fisheries, and the Treaty of the European Union (Hilborn et al., 2006). A number of government agencies, such as Fisheries and Oceans Canada (DFO), have adopted PA policies including an ecosystem-based approach to fisheries management. The North Atlantic Marine Mammal Commission (NAMMCO) and the International Whaling Commission (IWC) have similarly worked to develop international cooperation on conservation and management of cetaceans (Williams et al., 2014).